2015
DOI: 10.1007/s00737-015-0506-3
|View full text |Cite
|
Sign up to set email alerts
|

A case report demonstrating the efficacy of a comprehensive cognitive-behavioral therapy approach for treating anxiety, depression, and problematic eating in polycystic ovarian syndrome

Abstract: Despite elevated prevalence of anxiety and depression among women with polycystic ovarian syndrome (PCOS), there is a dearth of evidence-based psychotherapies to treat mood-related symptoms among this population. This case report describes the efficacy of The PCOS Workbook in treating symptoms of anxiety, depression, and problematic eating in a 19-year-old female previously diagnosed with PCOS. Using the cognitive-behavioral framework presented in the workbook, the participant experienced a significant reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…Most interventions included a focus on developing positive relationships. In some studies, relationship building was addressed through conflict resolution (Hickman et al., 2015), including within the family unit with a focus on addressing tensions that arise due to growing independence in adolescence (Correa et al., 2015; Cumba‐Avilés, 2017; McGrady & Hood, 2013). Other interventions emphasised drawing upon a positive social network, increasing social support and enhancing social connectedness (Rofey et al., 2009; Szigethy et al., 2007; Szigethy et al., 2004), and a focus on developing social skills, improving communication about blood glucose monitoring with parents (McGrady & Hood, 2013) and building positive relationships with health professionals (Cumba‐Avilés, 2017; Hickman et al., 2015; Szigethy et al., 2007; Szigethy et al., 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most interventions included a focus on developing positive relationships. In some studies, relationship building was addressed through conflict resolution (Hickman et al., 2015), including within the family unit with a focus on addressing tensions that arise due to growing independence in adolescence (Correa et al., 2015; Cumba‐Avilés, 2017; McGrady & Hood, 2013). Other interventions emphasised drawing upon a positive social network, increasing social support and enhancing social connectedness (Rofey et al., 2009; Szigethy et al., 2007; Szigethy et al., 2004), and a focus on developing social skills, improving communication about blood glucose monitoring with parents (McGrady & Hood, 2013) and building positive relationships with health professionals (Cumba‐Avilés, 2017; Hickman et al., 2015; Szigethy et al., 2007; Szigethy et al., 2004).…”
Section: Resultsmentioning
confidence: 99%
“…terminal cancer) OR conditions that one can recover from Other • Articles published in English thinking and maladaptive thought patterns (Hickman et al, 2015;Loades, 2015aLoades, , 2015bRofey et al, 2009;Rossell o & Jim enez-Chafey, 2006;Szigethy et al, 2007). Ten studies used cognitive restructuring to address illness-related thoughts and beliefs (Correa et al, 2015;Cumba-Avil es, 2017;McGrady & Hood, 2013;Rofey et al, 2009;Rossell o & Jim enez-Chafey, 2006;Szigethy et al, 2014;Szigethy et al, 2007;Szigethy et al, 2004) (Loades, 2015b) or maladaptive thoughts about medication administration (Hilliard et al, 2011). The content of maladaptive thoughts varied according to the illness physiology (e.g.…”
Section: Cbt Contentmentioning
confidence: 99%
“…Subsequently, a proactive approach to the treatment of psychological comorbidity should be preferred, since psychological treatments in women with PCOS are considered to have a positive effect on binge eating patterns, weight management, insulin resistance and hormonal imbalances [74,75]. In that context, tt has been suggested that the best approach combines psychological and pharmacological interventions [30], with the psychological treatments aimed at improving eating, body image and comorbid psychopathology, and the pharmacological and hormonal interventions decreasing androgen levels and reducing PCOS symptomatology [76].…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…Rofey et al, (2009) conducted a pretest-posttest study in 12 young individuals suffering from obesity, eating disorders, and depression; they concluded that CBT was effective for patients (10). Correa et al, (2015) reported the effect of CBT on the depression and anxiety of a 19-year-old girl suffering from PCOS (23). Therefore, considering the prevalence of depression (12,19,24) and obesity (1,2,13) in these patients and the necessity of preventive and therapeutic measures in this regard, as well as considering that based on searches conducted by the researcher, no study has been conducted in this field in Iran.…”
Section: Introductionmentioning
confidence: 99%